2022
DOI: 10.3390/molecules27227830
|View full text |Cite
|
Sign up to set email alerts
|

Bile Acids: Physiological Activity and Perspectives of Using in Clinical and Laboratory Diagnostics

Abstract: Bile acids play a significant role in the digestion of nutrients. In addition, bile acids perform a signaling function through their blood-circulating fraction. They regulate the activity of nuclear and membrane receptors, located in many tissues. The gut microbiota is an important factor influencing the effects of bile acids via enzymatic modification. Depending on the rate of healthy and pathogenic microbiota, a number of bile acids may support lipid and glucose homeostasis as well as shift to more toxic com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 169 publications
(324 reference statements)
0
2
0
Order By: Relevance
“…They contain a rigid hydrophobic steroid nucleus formed by four condensed rings, marked A, B, C (with six C atoms) and D (with five C atoms), as well as a flexible side alkyl chain terminated with a carboxyl group. Cycles A and B are linked in cis configuration, while cycles B-C, C-D are bound in trans configuration ( Figure 2 ) [ 41 , 42 , 43 , 44 , 45 , 46 , 47 ]. The binding in cis position of cycles A and B determines a curvature of the steroid skeleton, which allows the existence of two faces: α and β [ 48 , 49 ].…”
Section: Lipid-lowering Drugsmentioning
confidence: 99%
“…They contain a rigid hydrophobic steroid nucleus formed by four condensed rings, marked A, B, C (with six C atoms) and D (with five C atoms), as well as a flexible side alkyl chain terminated with a carboxyl group. Cycles A and B are linked in cis configuration, while cycles B-C, C-D are bound in trans configuration ( Figure 2 ) [ 41 , 42 , 43 , 44 , 45 , 46 , 47 ]. The binding in cis position of cycles A and B determines a curvature of the steroid skeleton, which allows the existence of two faces: α and β [ 48 , 49 ].…”
Section: Lipid-lowering Drugsmentioning
confidence: 99%
“…Bile acid metabolism is a sophisticated process that extends through the enterohepatic circulation, involving various stages such as bile acid synthesis in the liver, bile secretion, intestinal absorption, metabolic conversion, and hepatic reabsorption. [ 10 , 11 ] Emerging research has demonstrated that the bile acid profile undergoes specific changes in response to diverse disease states, [ 12 ] highlighting its potential as a biomarker for diagnosing complex conditions. In contrast to traditional total bile acid measurement, a thorough examination of the bile acid profile offers deeper insights into pathology, paving the way for accurate diagnosis and personalized treatment strategies.…”
Section: Discussionmentioning
confidence: 99%